2003
DOI: 10.1074/jbc.m303928200
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytes Produce 5-Chlorouracil and 5-Bromouracil, Two Mutagenic Products of Myeloperoxidase, in Human Inflammatory Tissue

Abstract: Oxidative damage to DNA has been implicated in carcinogenesis during chronic inflammation. Epidemiological and biochemical studies suggest that one potential mechanism involves myeloperoxidase, a hemeprotein secreted by human phagocytes. In this study, we demonstrate that human neutrophils use myeloperoxidase to oxidize uracil to 5-chlorouracil in vitro. Uracil chlorination by myeloperoxidase or reagent HOCl exhibited an unusual pH dependence, being minimal at pH ϳ5, but increasing markedly under either acidic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
147
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(148 citation statements)
references
References 48 publications
1
147
0
Order By: Relevance
“…Increased levels of several oxidation products have been found in AD brain including protein carbonyls (Smith et al 1998), o,o¢-dityrosine (Hensley et al 1998), AGEs (Vitek et al 1994;Yan et al 1994), 3-nitrotyrosine , lipid oxidation products Pratico et al 1998), and oxidized DNA (Mecocci et al 1994;Gabbita et al 1998). It is noteworthy that myeloperoxidase is capable of generating all of these products (Heinecke 1999;Henderson et al 2003) and that the localization of myeloperoxidase in the AD brain is similar to the localization of oxidative stress markers reported in the diseased brain: amyloid plaques (Smith et al 1994;Vitek et al 1994;Wong et al 2001), neurofilbrillary tangles (Good et al 1996;Sayre et al 1997;Smith et al 1997), and neuronal cytoplasm Smith et al 1997Smith et al , 1998. Our observation that myeloperoxidase is markedly unregulated in AD raises the possibility that the enzyme is one pathway for oxidative damage in this disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of several oxidation products have been found in AD brain including protein carbonyls (Smith et al 1998), o,o¢-dityrosine (Hensley et al 1998), AGEs (Vitek et al 1994;Yan et al 1994), 3-nitrotyrosine , lipid oxidation products Pratico et al 1998), and oxidized DNA (Mecocci et al 1994;Gabbita et al 1998). It is noteworthy that myeloperoxidase is capable of generating all of these products (Heinecke 1999;Henderson et al 2003) and that the localization of myeloperoxidase in the AD brain is similar to the localization of oxidative stress markers reported in the diseased brain: amyloid plaques (Smith et al 1994;Vitek et al 1994;Wong et al 2001), neurofilbrillary tangles (Good et al 1996;Sayre et al 1997;Smith et al 1997), and neuronal cytoplasm Smith et al 1997Smith et al , 1998. Our observation that myeloperoxidase is markedly unregulated in AD raises the possibility that the enzyme is one pathway for oxidative damage in this disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorinated amino acids and nucleobases identical to those formed by myeloperoxidase or HOCl in vitro have been detected in inflamed human tissue (22,23), but remarkably little is known about the reaction of HOCl with tryptophan residues in proteins (24 -26). Our studies demonstrate that HOCl targets tryptophan residues adjacent to glycine residues in the primary sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that in addition to oxidation, DNA bases can be damaged by inflammation-mediated reactive halogen species (7,8,10) under physiological conditions. The introduction of halogen atoms into a molecule complicates the appearance of the mass spectrum due to the higher abundance of heavy isotopes of chlorine and bromine (Fig.…”
Section: The Relative Peak Sizes Within the Ion Cluster Provide An Admentioning
confidence: 99%
“…Oligonucleotides were detritylated using 80% aqueous acetic acid at room temperature for 30 min and then purified using a Waters XTerra C-18 column and a gradient of 0 to 20% acetonitrile in water (44). The base composition of the oligonucleotides reported here was verified by formic acid hydrolysis followed by GC/MS analysis (7,10,14,16,21).…”
Section: Oligonucleotide Purificationmentioning
confidence: 99%
See 1 more Smart Citation